Prevalence of internet gaming disorder in adolescents: A meta-analysis across three decades - Fam, Jia Yuin * (Wiley, 2018)
Aims: The inclusion of “Internet gaming disorder (IGD)” in the fifth edition of Diagnostic and Statistical Manual of Mental Disorders (DSM-5) creates a possible line of research. Despite the fact that adolescents are vulnerable to IGD, studies had reported wide array of prevalence estimates in this population. The aim of this paper is to review the published studies on prevalence of IGD among adolescents. Methods: Relevant studies prior to March 2017 were identified through databases. A total of 16 studies met the inclusion criteria. Results: The pooled prevalence of IGD among adolescents was 4.6% (95% CI = 3.4%-6.0%). Male adolescents generally reported higher prevalence rate (6.8%, 95% CI= 4.3%-9.7%) than female adolescents (1.3%, 95% CI = 0.6%-2.2%). Subgroup analyses revealed that prevalence estimates were highest when studies were conducted in: (i) 1990s, (ii) use DSM criteria for pathological gambling, (iii) examine gaming disorder, (iv) Asia, and (v) small samples (<1000). Conclusion: This study confirms the alarming prevalence of IGD among adolescents, especially among males. Given the methodological deficits in past decades (such as reliance on DSM criteria for “pathological gambling”, inclusion of the word “Internet”, and small sample sizes), it is critical for researchers to apply a common methodology for assess this disorder.